Biotransformation of ω-fatty acid from Clarias gariepinus using Psuedomonas aeruginosa - Omar, Muhammad Nor; Shaban, Norhayati; Bakar, Latifah Munirah; Zuberdi, Ahmad Muzammil (Academic Information Press, 2012)
Study on biotransformation of -fatty acid from fish oil was carried out. Pseudomonas aeruginosa has been chosen to be the biocatalyst for biotransformation of w fatty acids extracted from Malaysian catfish, Clarias gariepinus. The lipid from freeze-dried catfish flesh was extracted using a modified Folch method and the mixture of chloroform and methanol was used as a solvent. The crude lipid substrate was added to the bacterial culture and incubated for 4 days. After conversion, the products were analyzed by using gas chromatography and mass spectrometer (GC-MS). The analytical result showed that several fatty acids and cholesterol were found in the product. However, the fatty acids and cholesterol contents before and after biotransformation were different. The cholesterol content increased while -fatty acid contents decreased after biotransformation process. It can be concluded that the bacterial cells had oxidized the -fatty acids to yield precursors which can be utilized as starting materials for the bioconversion to cholesterol.